Sustainable Management and Business in the Area of Grocery Shopping - The Efficiency of Grocery Shopping (EOGS) Project - Bongard, Stefan; Dachkilgov, Farisa; Düthmann, Fynn; Flick, Elias; Mardani, Keyvan; Zakys, Armin (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Net sales in the German food retail sector exceeded EUR 250 billion in 2022. This market is therefore not only interesting due to its sheer size, but also due to recent developments in online retail. In addition to the dominance of traditional store sales, online delivery services and providers that deliver groceries to your doorstep in just a few minutes are alternatives for customers. Various perspectives need to be examined to assess the sustainability of business and trade in this sector. On the one hand, it is about providers with a focus on delivery services, who are competing for customers' favour with various concepts and delivery modalities. On the other hand, the focus is on consumers, who now have a range of alternatives for purchasing food. Additionally, one can investigate how sustainable a delivery service purchase is compared to a stationary purchase. Methodologically, the project is carried out with practical case studies with a recording and analysis tool (EoGS-tool). The first stage of the project will focus on testing the practicability and usability of the tool and evaluating the initial results. In a second stage, the recording and evaluation of purchases is to be expanded through cooperation with other universities.